Locating the global: spaces, networks and interactions from the seventeenth to the twentieth century - Weiss, Holger (De Gruyter Oldenbourg, 2020)
Frontmatter -- On the Series -- Contents -- 1 Locating the Global: Articulations, Encounters, and Interactions -- 2 A Forgotten Emporium: Commercial Aspirations and Transnational Mercantile Networks in Seventeenth- Century Glückstadt -- 3 Global Materials, Contact Zones, and Imitation: The Making of Metal Commodities in Eighteenth-Century Sweden -- 4 Coffee and Coffee Surrogates in Sweden: A Local, Global, and Material History -- 5 Circulating Heterodox Medicine: Globalizing and Localizing Naturopathy in Interwar Finland -- 6 Stocktaking at Christiansborg: Metals and Slaves in the Danish Atlantic Trade at the Mid-Eighteenth Century -- 7 Copper on the Move: A Commodity Chain between Sweden and France, 1720–1790 -- 8 Encountering Mid-Eighteenth Century Morocco from Below: Slavery, Race, and Religion in two Scandinavian Captivity Narratives -- 9 Eurafrican Mobility and Encounters with Race, ca. 1880–1920 -- 10 Muslim Scholars Living in Three Worlds: West African Muslims and the Imposition of the European Colonial Order -- 11 Russia in the Global Parliamentary Moment, 1905–1918: Between a Subaltern Empire and an Empire of Subalterns -- 12 A Neutral Place? Anti-Colonialism, Peace, and Revolution in Stockholm, 1917 -- 13 Ethiopia in Swedish Press in the Run-up to the Italo-Ethiopian War, 1935/36 -- 14 Cartographic Histories of the Western Territorialization of Northern Australia, 1840s–1900s: Global Circuits of Knowledge and the Mapmakers’ Craft -- 15 National History and Big History: Väinö Auer, the Finnish Nationalist and the Global Environmentalist -- 16 Global Hubs on the Move: Nineteenth- Century World’s Fairs as Spaces of Imagining the World -- 17 Visualizing Sweden at the 1937 World Fair in Paris -- 18 National Museums and the Wider World: The Exclusion of Non-Western Collections at the National Museum of Finland -- 19 A Contested Global Memory Space: The Establishment of the National Museum of Ghana -- List of Contributors -- Index
Gesehen am 28.06.2021
Keywords: Aufsatzsammlung; Regionalwirtschaft; Regionale Identität; Globalisierung